1996
DOI: 10.1111/j.1439-0523.1996.tb00924.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of low‐temperature‐sensitive sterility in indica‐japonica rice hybrids

Abstract: Low-temperature-sensitive steriUty has become one of the major obstacles in indica-japonica hybrid rice breeding. The objectives of this paper were to evaluate the extent of the fertility reduction and to determine the genetic basis of low-temperature-sensitive sterility. Seventeen varieties were crossed in various ways to produce 21 F|S including 16 indica-japonica hybrids. Fertility of the F]S and their parents was examined under both high and low temperature conditions. Considerable reduction in spikelet fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…japonica. These three varieties are regarded as typical indica or japonica, and were recommended and used as testers for compatibility analyses (Liu et al 1996). Nanjing 11 was crossed with Akihikari to produce an inter-subspecific hybrid, and with IR36 to produce an intra-subspecific hybrid.…”
Section: Genetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…japonica. These three varieties are regarded as typical indica or japonica, and were recommended and used as testers for compatibility analyses (Liu et al 1996). Nanjing 11 was crossed with Akihikari to produce an inter-subspecific hybrid, and with IR36 to produce an intra-subspecific hybrid.…”
Section: Genetic Materialsmentioning
confidence: 99%
“…It is known that the majority of the indica/japonica hybrids are partly sterile, with the spikelet fertility mostly in the range of 30-60% (Liu et al 1996). It has also been observed that strong heterosis exists in many indica/japonica hybrids in both vegetative and reproductive growth, which has attracted the attentions of rice breeders for several decades (Yang et al 1962;Chu et al 1964;Yuan 1987).…”
Section: Introductionmentioning
confidence: 96%
“…Parzies et al (2000) reported higher outcrossing rates under fluctuating rainfall conditions. Light intensity has been shown to modify the outcrossing rate in other self-pollinated species such as wheat (Demotes-Mainard et al 1995) and rice (Li et al 1996). Low population density reduced outcrossing in the cross-pollinated crop Cuphea laminuligera (Krueger and Knapp 1991).…”
Section: Introductionmentioning
confidence: 98%
“…f was estimated by the maximum likelihood method proposed by Li and Horovitz (1953) (Nelson et al, 1995a,b (Li et al, 1996) and winter wheat (Demotes-Mainard et al, 1995). Demotes-Mainard et al (1995) (Fisher, 1958 (David et al, 1993;Ronfort and Couvet, 1995).…”
Section: Introductionmentioning
confidence: 99%